Kunjungan Presiden Xi Jinping ke Indonesia dari Perspektif Media di Indonesia dan Tiongkok: Suatu Kajian Pendahuluan - Lalisang, Yeremia (Global: Jurnal Politik Internasional, 2013)
This research note compares the way Chinese and Indonesian newspapers covered the visit of Xi Jinping, the President of the People's Republic of China, to Indonesia at October 2nd - 3rd, 2013. It analyzes news and articles related to the visit appeared in four major newspapers both in China and Indonesia, namely, China Daily, South China Morning Post, KOMPAS, and The Jakarta Post. It finds that, in covering the visit, China Daily, the overseas mouthpiece of Chinese Government, only focused on the positive development of the bilateral relations, the importance to upgrade the economic relations, particularly the bilateral trade, and the Indonesia's notable role in improving China - ASEAN relations. On the other hand, the other three medias covered the visit from diverse point of views, and thus, expanded the news coverage. They not only reported the positive developments, but also mentioned the problems and challenges faced by both Indonesia and China in maintaining their relations and the Indonesian's pessimistic and suspicious views of China.